Effects of water walking on the anthropometric and metabolic aspects in young obese individuals - Maria de Fatima Aguiar Lopes; Paulo Cesar Barauce Bento; Leilane Lazzaroto; André Félix Rodacki; Neiva Leite (Universidade Federal de Santa Catarina, 2015)
Water-based exercise has been recommended for obese individuals due to reduced joint load. The aim of this study was to determine the effects of twelve weeks of water walking (WW) with or without nutritional guidance on anthropometric and metabolic variables in young obese individuals. Seventy-three young obese individuals of both genders (10 - 16 years) were randomly assigned in one of the three groups: Water walking and nutritional guidance group (WWN; n=23), Water walking group (WW; n=22) and Control group (CG; n=28). Body mass, height and waist circumference were assessed. Body Mass Index z score (BMI-z) was calculated, also analyzing total blood cholesterol levels (TC) and its fractions, high density cholesterol (HDL-C), low density cholesterol (LDL-C), triglycerides (TG) and fasting glucose before and after the training program. A two-way repeated-measures analysis of variance (ANOVA) was applied to compare groups and post hoc Tukey`s test was used for multiple-comparison in case of significant differences. Analysis of covariance was applied when differences were detected in the pretest. The significant level was set at p<0.05. The distance per exercise session increased from 377 to 829 meters from beginning to the end of the training period. The lipid profile and fasting glucose did not change after training (p>0.05). Reduction in total cholesterol in the walking group with nutritional guidance was observed (p<0.05). Water walking training can be considered as alternative to improve the physical fitness, being particularly effective for cholesterol reduction when combined with nutritional guidance.